2018
DOI: 10.1002/jcp.27172
|View full text |Cite
|
Sign up to set email alerts
|

PD‐1/PD‐L1 immune checkpoint: Potential target for cancer therapy

Abstract: Recent studies show that cancer cells are sometimes able to evade the host immunity in the tumor microenvironment. Cancer cells can express high levels of immune inhibitory signaling proteins. One of the most critical checkpoint pathways in this system is a tumor-induced immune suppression (immune checkpoint) mediated by the programmed cell death protein 1 (PD-1) and its ligand, programmed death ligand 1 (PD-L1). PD-1 is highly expressed by activated T cells, B cells, dendritic cells, and natural killer cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
262
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(265 citation statements)
references
References 132 publications
2
262
0
1
Order By: Relevance
“…Lieping Chen et al identified and cloned the human B7-H1 gene in the year 1999 and found that this molecule could negatively regulate T cell function through the induction of IL-10 [16]. Accumulating evidence shows that PD-L1 plays a central role in the regulation of the immune responses in the tumor microenvironment [50]. PD-L1 binds to PD-1 and inhibits T cell proliferation and its cytokine secretion and leads to apoptosis, anergy, and exhaustion of T cells [51].…”
Section: Discussionmentioning
confidence: 99%
“…Lieping Chen et al identified and cloned the human B7-H1 gene in the year 1999 and found that this molecule could negatively regulate T cell function through the induction of IL-10 [16]. Accumulating evidence shows that PD-L1 plays a central role in the regulation of the immune responses in the tumor microenvironment [50]. PD-L1 binds to PD-1 and inhibits T cell proliferation and its cytokine secretion and leads to apoptosis, anergy, and exhaustion of T cells [51].…”
Section: Discussionmentioning
confidence: 99%
“…Next to this, PD-1 ligation alters the metabolic program of activated T cells thereby generating a more oxidative microenvironment [48,49]. PD-1 signaling is well understood and has been recently extensively reviewed [50], while only limited information on PD-L1 signaling is available. However, there exists evidence of a reverse signaling via cross-binding with mAbs.…”
Section: Pd-1/pd-l1-mediated Signal Transduction and Its Functionmentioning
confidence: 99%
“…Together, the role of this pathway is to suppress the activation of T cells, when activated by its circulating ligands, occurring in the context of infection or tumor progression [4,5]. When PD-1 receptors are blocked, T cells initiate an inflammatory response against the tumor [6].…”
Section: Introductionmentioning
confidence: 99%